THE IDEAS OF THE NATIONAL REVIVAL IN THE UKRAINIAN MOVEMENT OF RESISTANCE OF THE 60-s OF THE XX-th CENTURY - Білоус, Л. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In this article problems of national revival in the activity of Ukrainian national movement of resistance in the 1960th are analyzed.